Processo judicial eletrônico: novos tempos para o trabalho da advocacia? - Velasco Junior, Estanislau (2013)
This research investigates how interactions occur and the relationship between Technology and the Work of the Lawyer. The study aims to analyze the current conditions of work of advocacy from the changes brought by Judicial Process Electronic - PJE. We seek to present the quantum the PJE has conditioned the daily praxis of advocacy activity. It has as theoretical assumption that the Work and Technology does not determine human action and therefore humans free to control the facilities brought by technology which should in theory provide the improvement in the material conditions of life people. This is research from open questionnaires that allow both a qualitative analysis of the content of the written reports, as some quantification via consolidation of replies. It analyzes the transformations caused by computerization of the judicial process in your new electronic form, these changes occurred since the enactment of Law 11.419/2006 and the restructuring of the work of Brazilian advocacy in recent years. The problem we intend to answer is the following: What is the emancipatory potential of technology to the work of the lawyer? At the end of the study presents the results obtained in the research regarding: intensification of labor lawyer, modifications in the structure of advocacy firms, lawyers 'main difficulties with the PJE, changes in work productivity of lawyers, lawyers' perception regarding impacts of the implementation of PJE in health and some gender implications between men and women lawyers to get to work with the Judicial Process Electronic.